Metabolite V, an epoxide species is a minor circulating metabolite in humans following a single oral dose of deflazacort. Issue 6 (22nd October 2020) - Kong, Ronald; Ma, Jiyuan; Beers, Brian; Kaushik, Diksha; Lin, E; Goodwin, Elizabeth; Colacino, Joseph; Bibbiani, Francesco
Abstract: Deflazacort (Emflaza) was approved in the United States in 2017 for the treatment of the Duchenne muscular dystrophy in patients aged 2 years and older. Several deflazacort metabolites were isolated and identified from rats, dogs, monkeys, and humans. Among them, 1ß, 2ß‐epoxy‐3ß‐hydroxy‐21‐desacetyl deflazacort, referred to as Metabolite V, was reported to be one of the major circulating metabolites in humans. However, its quantitative distribution in plasma was not fully characterized. The objective of this study was to determine deflazacort plasma pharmacokinetics, metabolite profiles and their quantitative exposures in humans following a single oral dose. Six healthy male subjects were each administered a single oral dose of 60 mg [ 14 C]‐deflazacort. Plasma and urine were collected and deflazacort metabolites in plasma were quantified by high performance liquid chromatography radio‐profiling followed by liquid chromatography‐mass spectrometry characterization. Metabolite V was isolated from urine and its structure was further confirmed by nuclear magnetic resonance analysis. These analyses demonstrated that deflazacort was not detectable in plasma; of the eight circulating deflazacort metabolites identified or characterized, the pharmacologically active metabolite 21‐desacetyl deflazacort and inactive metabolite 6ß‐hydroxy‐21‐desacetyl deflazacort accounted for 25.0% and 32.9% of the 0‐24 hours plasma total radioactivity, respectively, while Metabolite V, an epoxide species, was a minor circulating metabolite, representing only about 4.7% of the total plasma radioactivity. Abstract : To determine metabolite profiles of deflazacort following a single oral dose of deflazacort in healthy human subjects. Six healthy male subjects were each administered a single oral dose of 60 mg [ 14 C]‐deflazacort. Deflazacort metabolites in plasma were quantified. Metabolite V was isolated from urine and its structure was further confirmed by NMR. 21‐Desacetyl deflazacort and 6ß‐hydroxy‐21‐desacetyl deflazacort were the major metabolites. All others were minor plasma metabolites. Contrary to a previous report, Metabolite V, an epoxide, was a minor circulating metabolite.